2019
DOI: 10.1016/j.jaci.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic caspase activation and recruitment domain 11 (CARD11) mutations associated with diverse immunologic phenotypes with or without atopic disease

Abstract: These results illuminate a broader phenotypic spectrum associated with CARD11 mutations in human subjects and underscore the need for functional studies to demonstrate that rare gene variants encountered in expected and unexpected phenotypes must nonetheless be validated for pathogenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 37 publications
7
114
0
Order By: Relevance
“…Because heterozygous relatives of patients with severe combined immunodeficiency with complete autosomal recessive CARD11 deficiency seem to be healthy, the CARD11 locus probably displays no haploinsufficiency, at least with high penetrance. 6,7 Therefore the results presented by Dorjbal et al 2 suggest that only 40% (10/25) of the suspected CARD11 disease-causing variants are likely to cause disease. Supporting this conclusion, 14 (93%) of the 15 non-DN LOF alleles are present in the gnomAD database, although most have a minor allele frequency of less than 10 23 (Fig 1, C).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Because heterozygous relatives of patients with severe combined immunodeficiency with complete autosomal recessive CARD11 deficiency seem to be healthy, the CARD11 locus probably displays no haploinsufficiency, at least with high penetrance. 6,7 Therefore the results presented by Dorjbal et al 2 suggest that only 40% (10/25) of the suspected CARD11 disease-causing variants are likely to cause disease. Supporting this conclusion, 14 (93%) of the 15 non-DN LOF alleles are present in the gnomAD database, although most have a minor allele frequency of less than 10 23 (Fig 1, C).…”
mentioning
confidence: 97%
“…One of these variants was recurrent and had been reported before, 8 but the other 24 were previously unknown, and 3 of these variants were found in more than 1 kindred. 2 By expressing each of the 25 mutant alleles in a CARD11-deficient Jurkat cell line, the authors showed that 14 of these alleles impaired NF-kB activation on CD3/CD28 stimulation, completely for 8 of the alleles and partially for the other 6, whereas 2 enhanced NF-kB activation on stimulation. Ten of these 14 LOF variants acted through a DN effect on the wild-type allele for NF-kB activation.…”
mentioning
confidence: 99%
“…Similar to some patients with PGM3 deficiency, individuals with bi‐allelic loss‐of‐function mutations in CARD11 , MALT1 , and BCL6 have all been described to present with combined immunodeficiency with T lymphopenia . More recently, we and others have described heterozygous loss‐of‐function and dominant negative mutations in CARD11 that result in atopic dermatitis and associated allergic diatheses including elevated IgE, allergic asthma, and immediate hypersensitivity to foods, as well as variable humoral immune deficiency, cutaneous viral infections, autoimmunity, and lymphoma . In these patients, CD4 + lymphocytes fail to upregulate ASCT2 and display reduced mTORC1 activation as determined by reduced phosphorylation of S6 kinase in response to PMA stimulation .…”
Section: When Atopy Is In the Card(s)mentioning
confidence: 65%
“…[52][53][54][55][56] More recently, we and others have described heterozygous loss-of-function and dominant negative mutations in CARD11 that result in atopic dermatitis and associated allergic diatheses including elevated IgE, allergic asthma, and immediate hypersensitivity to foods, as well as variable humoral immune deficiency, cutaneous viral infections, autoimmunity, and lymphoma. 51,57,58 In these patients, CD4 + lymphocytes fail to upregulate ASCT2 and display reduced mTORC1 activation as determined by reduced phosphorylation of S6 kinase in response to PMA stimulation. 51 These patients also have associated decreases in Th1-associated cytokines ex vivo and impaired in vitro T cell proliferation.…”
Section: When Atopy Is In the C Ard (S)mentioning
confidence: 99%
“…Clinical immunologists should be aware that some PIDD genes, such as STAT1, CARD11, and IRF8, are associated with both dominant and recessive inheritance of pathogenic variants and interpret the presence of one or multiple variants in such genes accordingly. [136][137][138][139] Furthermore, distinct heterozygous pathogenic variants within the same gene can also produce completely different PIDDs through either loss of function or altered function (eg, STAT3 variants that result in hyper-IgE syndrome vs gain-of-function disease or WAS variants that cause Wiskott-Aldrich syndrome vs X-linked neutropenia). OMIM serves as an excellent resource for examining different Mendelian patterns and phenotypic presentations for pathogenic variants within a single gene.…”
Section: Variant-based Computational Datamentioning
confidence: 99%